Cassava (Manihot esculenta Crantz) prolamine isolation and partial purification. - Estores, Febe B.
More than 600 M people in Asia, Africa, and Latin America depend on cassava, mainly on its tubers, as their staple food. Those people that feed mainly on cassava often suffer from diseases like protein energy malnutrition because cassava is low in protein content -- about 1-3 percent on average. There is therefore a need to improve the protein content of this crop. For this to be possible, a better understanding of the proteins of cassava is needed., In this study, prolamine, one of the proteins found in cassava tuber, was isolated and partially purified. The protein was islated through Osborne fractionation and purified through gel filtration chromatography. The molecular weights of the components of prolamine were estimated through Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis. The estimated molecular weights of the protein components were found out to be kDa, 66 kDa, and 87 kDa.